Pengembangan Sistem Pelayanan Klinik Budhi Pratama Gedong Berbasis Web dengan Metode Rapid Application Development (RAD) (Journal Digital Technology Trend, 2024)
Budhi Pratama Gedong Clinic faces significant challenges in the manual handling of patient data and report recording, leading to inefficiencies and slow operational processes. To address these issues, the development of a computerized system is essential for collecting, storing, and processing data to generate actionable information that can enhance healthcare services. This computerized system is also expected to reduce operational costs by minimizing the reliance on paper-based records. Located at Jalan Raya Tengah No. 26 RT 6/RW 1 Gedong Pasar Rebo, East Jakarta, the clinic provides various health services, including medication procurement, which currently relies on manual processes. The implementation of a web-based service system using the Rapid Application Development (RAD) methodology with XAMPP is projected to streamline operational processes and improve data reporting. The objectives of this study include facilitating easier patient registration, expediting medical record retrieval, simplifying medication management, and increasing the accuracy of patient payment processing. Furthermore, the developed system aims to integrate a comprehensive database to efficiently document and manage data on patients, doctors, clinic staff, and medications, thereby providing a user-friendly platform for healthcare providers and enhancing overall patient care